2007
DOI: 10.1007/s00439-007-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic admixture, adipocytokines, and adiposity in Black Americans: the Health, Aging, and Body Composition study

Abstract: Adipocytokines are a subset of cytokines produced by adipose tissue and are associated with risk of type II diabetes and atherosclerosis. Levels of adipocytokines differ between Black and White Americans, even after adjustment for differences in adiposity, diseases associated with adipocytokines including type 2 diabetes and cardiovascular disease, and general socioeconomic status indicators such as income. We used a series of ancestry informative markers to estimate genetic ancestry in a population-based stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
6
25
0
Order By: Relevance
“…The African American cohort in our study had a mean of 15% European admixture, which is consistent with previous reports of a range of 7% to 23% European admixture among U.S. African Americans (14)(15)(16). Of note, the estimates of 4% European and 1% Native American ancestry in the Nigerian population is likely due to bias in MLE due to the limited number of markers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The African American cohort in our study had a mean of 15% European admixture, which is consistent with previous reports of a range of 7% to 23% European admixture among U.S. African Americans (14)(15)(16). Of note, the estimates of 4% European and 1% Native American ancestry in the Nigerian population is likely due to bias in MLE due to the limited number of markers.…”
Section: Discussionsupporting
confidence: 90%
“…Genetic studies have shown that African Americans form a diverse group with percent European admixture estimated to range between 7% and 23% (14)(15)(16). Genotyping of self-identified African Americans participating in the Cardiovascular Health Study revealed that among self-reported Africans there are differences in genetic ancestry that are correlated with some clinically important endpoints (15).…”
Section: Introductionmentioning
confidence: 99%
“…COMPASS includes cohort studies–Atherosclerosis Risk in Communities (ARIC) Study 15 , Cardiovascular Health Study (CHS) 16 , Dynamics of Health, Aging and Body Composition Study (HABC) 17 , and the Women’s Health Initiative (WHI) 18 ,–and case-control studies–Genetics of Early Onset Stroke (GEOS) 19 , Ischemic Stroke Genetics Study (ISGS) 20 , Vitamin Intervention for Stroke Prevention (VISP) 21 and Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) 22 , –as well as an affected sibpair study–Siblings with Ischemic Stroke Study (SWISS) 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were well functioning men and women aged 70–79 years sampled from Medicare beneficiaries living in or around Alleghany County, Pennsylvania and Memphis, Tennessee. Inclusion and exclusion criteria have been described in detail elsewhere 27. Of a sample of 3075 subjects, 1281 were self reported African Americans.…”
Section: Methodsmentioning
confidence: 99%